Impact of Career Salience on Employees Job Involvement, Analyzing the Moderating Role of Organization Citizenship Behavior - ROQIA MALIK; DR. MUHAMMAD ZIA-UR-REHMAN; DR. FAHAD SULTAN; MOHAMMAD UMAIR KHAN (Journal of Business & Tourism, 2021)
The current study identifies the factor that affecting the organization citizenship behavior and its employee’s job involvement. The study gives significance value to the literature that it provides compete discussion and information on organization citizenship behavior and its antecedents and consequences. The purpose of the study is to find out the impact of career salience on employees job involvement, analyzing the moderating role of organization citizenship behavior. Questionnaire method is used for data collection. Researcher collects the data from middle and lower level of employees on different organization. The total 44 questions asked from the middle and lower level of employees in Rawalpindi Islamabad Pakistan. The total data was collected through questionnaire from sample of 250 individuals and total 240 of respondent data was used for analysis. The result of this study indicated that there are significance relationship between independent and dependent variables and moderation was checked through (Baron & Kenny, 1986) condition. To test the reliability of the items cronbach’s alpha was used and testing the hypothesis of the study regression analysis was used. Further result show that the career salience, employees job involvement mediating effect of organization citizenship behavior.